Perancangan Aplikasi Absensi Berbasis Web pada Alwi College - Daffa Yudha Musyaffa; Albert Cahayadi; Novan Wijaya (Universitas Multi Data Palembang, 2026)
Digitalization has brought significant changes in various fields, including education. Since the COVID-19 pandemic, the use of technology in learning systems has increased rapidly. One important aspect of academic management is the attendance system, which, when conducted manually, is considered inefficient and prone to errors. This study aims to design a web-based attendance system for Alwi College tutoring center to improve the efficiency and organization of student attendance records. The Waterfall method is applied, consisting of requirement analysis, system design, design implementation, and design testing stages. The results of this study are in the form of a structured design for a web-based attendance system, including user interface design, attendance process flow, and database design. In conclusion, the proposed attendance system design can serve as an effective foundation for developing a more structured, accurate, and integrated attendance management system at Alwi College.